The Management of Staffs’ Capabilities on Information Technology toward Project Oriented, and Teamwork to Project Cost Reduction - Kuntonbutr, Chanongkorn; Jaturat, Natnarong; Kuntonbutr, Sudaporn (NIDA Development Journal, 2018)
From the concept of using information technology (IT) is benefit to management. This study explores this assumption in term of whether capability of the IT staffs, project oriented can support teamwork oriented, and reduce cost of the project. A model was instructed to explain the relationship between IT staffs capabilities, project oriented, teamwork oriented, and project cost reduction. The results indicate that the capability of the IT staffs have a direct significant positive influence on both project oriented and teamwork oriented. Project oriented has also a significant positive affect to teamwork oriented, and consequently affect to overall project cost reduction.